The virulence regulator VirB from Shigella flexneri uses a CTP-dependent switch mechanism to activate gene expression - Jakob, Sara; Steinchen, Wieland; Hanßmann, Juri; Rosum, Julia; Langenfeld, Katja; Osorio Valeriano, Manuel; Steube, Niklas; Giammarinaro, Pietro Ivan; Hochberg, Georg K. A.; Glatter, Timo; Bange, Gert; Diepold, Andreas; et al. (Nature Communications, 2024)
The transcriptional antisilencer VirB acts as a master regulator of virulence gene expression in the human pathogen Shigella flexneri. It binds DNA sequences (virS) upstream of VirB-dependent promoters and counteracts their silencing by the nucleoid-organizing protein H-NS. However, its precise mode of action remains unclear. Notably, VirB is not a classical transcription factor but related to ParB-type DNA-partitioning proteins, which have recently been recognized as DNA-sliding clamps using CTP binding and hydrolysis to control their DNA entry gate. Here, we show that VirB binds CTP, embraces DNA in a clamp-like fashion upon its CTP-dependent loading at virS sites and slides laterally on DNA after clamp closure. Mutations that prevent CTP-binding block VirB loading in vitro and abolish the formation of VirB nucleoprotein complexes as well as virulence gene expression in vivo. Thus, VirB represents a CTP-dependent molecular switch that uses a loading-and-sliding mechanism to control transcription during bacterial pathogenesis.